PENGARUH INFLASI, KURS, BI RATE, OBLIGASI DAN PPh BADAN TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) (Studi Kasus Pada Perusahaan Manufaktur Sektor Property Dan Real Estate Yang Terdaftar Di BEI Tahun 2015-2017 ) (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT            For three years starting from the period of 2015-2017 composite stock price index experienced a fluctuation. At this time the research the author will discuss about inflation, exchange rate, the BI Rate, bonds and Corporate income tax that can be under the composite stock price index. This thesis research using this type of Explanatory Reseach study take sampling of populations by using purposive sampling technique by using two types of variables, i.e. Dependent Variable (the variable) and variables The independent (free variables).  The results from this study is variable Inflation effect significantly to JCI, the variable exchange rate do not affect significantly to JCI, the BI Rate variable significant effect against the JCI, variable bonds effect significantly to JCI, variable Corporate income tax do not affect significantly to JCI.  Key words: inflation, exchange rate, the BI Rate, bonds, Corporate income tax, the composite stock price index.